Urban Refugee Protection and the 2030 Sustainable Development Agenda in Ethiopia: Challenges and Missing Links (African Human Mobility Review, 2025)
Urban refugees in Ethiopia face persistent challenges despite progressive legal and policy reforms, including the 2019 Refugee Proclamation, the Comprehensive Refugee Response Framework, and some alignment with the 2030 Sustainable Development Goals. This study examined the gaps between policy commitments and lived realities by integrating desk reviews, key informant interviews with government and humanitarian actors, and in-depth interviews with 21 refugees from diverse nationalities in Addis Ababa. Findings reveal partial successes in economic inclusion, education, healthcare, documentation, and social participation, yet structural, administrative, and legal barriers constrain meaningful access to livelihoods, housing, services, and social networks. Social capital mediates refugees’ ability to navigate these challenges, while disparities in documentation, language, and market access exacerbate vulnerability. The study concludes that Ethiopia’s urban refugee protection system exhibits implementation gaps that undermine Sustainable Development Goal-aligned outcomes and emphasizes the need for coordinated, inclusive, and context-sensitive policies that translate formal rights into substantive capabilities and equitable integration opportunities.